The Governance of UK Dairy Antibiotic Use: Industry-Led Policy in Action - Begemann, Stephanie; Watkins, Francine; Van Hoyweghen, Ine; Vivancos, Roberto; Christley, Robert; Perkins, Elizabeth (Frontiers in Veterinary Science, 2020)
This article analyses the progress made in the UK with regard to tackling antibiotic ‘misuse and overuse’ in food-producing animals. Moving beyond statistical realities, the paper examines how the UK’s industry-led policy approach is shaping practice. Using a multi-sited ethnography situated in Actor Network Theory and Callon’s sociology of markets, the UK dairy supply chain policies and practices were studied. Findings reveal that dairy industry policies only partially address the complex network of people, animals and the environment in which dairy antibiotics circulate. Antibiotic ‘misuse and overuse’ in agriculture is far from a behavioural matter, with solely farmers and veterinarians to blame. Instead, antibiotic use in food animals is embedded in complex economic networks that constrain radical changes in dairy husbandry management and antibiotic use on farms. More attention towards the needs of the dairy supply chain actors and wider environmental considerations is essential to reduce the dairy sector’s dependency on antibiotics and support transition towards responsible farming in the UK.